Tính toán, dự đoán suy hao, và tìm vùng phủ sóng tối ưu trong thông tin vô tuyến - Lê, Đăng Giáp (Trường Đại học Đà Lạt, 2012)
The characteristic of the radio transmission channel is random and invisible, requires complicated calculations and simulations. Therefore, the modeling of transmission channel is the most important stage of the process of designing the radio systems. Commonly, this stage is carried out with the statistic method for the results of practical measurements. This method takes a lot of time and is almost inaccurate because the number of sample is limited and it is difficult to apply it on a large area.